Magnetic gradient aerogel-membrane composite material and application thereof
By introducing magnetic gradient aerogel-film composite material into electromagnetic shielding material, a gradient absorption-reflection-reabsorption loss mechanism is constructed, which solves the problems of severe electromagnetic wave reflection and short transmission path, achieves a highly efficient and low-reflection electromagnetic shielding effect, and enhances the material's resistance to physical attacks.
Patent Information
- Application Number
- CN202511643265.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-11
- Publication Date
- 2026-02-06
AI Technical Summary
Existing electromagnetic shielding materials suffer from severe electromagnetic wave reflection in high-frequency environments, leading to secondary pollution. Furthermore, their short transmission paths and insufficient loss mechanisms make it difficult to achieve efficient and low-reflection electromagnetic shielding.
By employing magnetic gradient aerogel-membrane composite materials, a loss mechanism of gradient absorption-reflection-reabsorption is constructed by introducing a highly conductive MXene film and CNF/CNT/Fe3O4 aerogel into an asymmetric composite film and using magnetic induction to control the distribution of magnetic fillers, thereby extending the electromagnetic wave transmission path.
It significantly improves electromagnetic shielding and absorption efficiency, reduces electromagnetic wave reflection, enhances the material's resistance to physical attacks and compressive strength, and achieves low-reflection electromagnetic shielding.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of electromagnetic shielding composites, in particular to a magnetic gradient aerogel-film composite with low reflection and high efficiency electromagnetic shielding performance and a preparation method thereof. BACKGROUND
[0002] With the development of science and technology, the development of numerous electronic devices has improved the quality of human life, and electronic devices have gradually developed towards multifunctional, precise, lightweight and integrated. In high-frequency working environment, the heat generated by electronic components accumulates rapidly, which seriously affects the precision and service life of the equipment. At the same time, the problem of electromagnetic pollution is also becoming increasingly serious, which has a certain impact on the precision and service life of electronic devices, human health and the environment. Therefore, it is urgent to develop electromagnetic shielding composites with excellent performance to effectively alleviate this increasingly serious problem.
[0003] Although filled conductive polymer composites with the advantages of light weight, easy processing and corrosion resistance have made significant progress in the field of electromagnetic shielding, most researches still focus on improving the electrical conductivity of the material to improve the shielding effect. Excessive pursuit of the electrical conductivity of the composite material may lead to impedance mismatch between the material and the air, thereby causing a large amount of electromagnetic wave reflection, intensifying secondary electromagnetic pollution and posing a potential threat to other electronic devices. In addition, with the deepening of the public's awareness of electromagnetic pollution, the performance requirements of electromagnetic shielding materials are transforming, i.e. from pure high shielding performance to low reflection and high wave absorption characteristics, which requires electromagnetic shielding materials to have the ability to reduce electromagnetic wave reflection and reduce secondary pollution.
[0004] The high density, difficulty in processing and weak corrosion resistance of metal fillers limit their application in highly integrated electronic devices. Accordingly, in recent years, MXene has shown considerable application potential in the field of electromagnetic shielding due to its excellent characteristics such as rich surface functional groups, large specific surface area and high electrical conductivity. Cellulose nanofiber (CNF) has been widely used due to its excellent mechanical properties, low density, environmental protection, biodegradability and renewability. This makes CNF an excellent substitute for synthetic materials such as steel, Kevlar fiber and polyvinyl alcohol. However, the high electrical conductivity of MXene brings excellent electromagnetic shielding performance, but it may also cause secondary electromagnetic pollution. Therefore, it is currently an urgent problem to obtain high-performance low-reflection electromagnetic shielding composites through a simple process.
[0005] The construction of the asymmetric structure and the addition of magnetic porous fillers have a positive effect on optimizing the impedance matching between the composite membrane and air. Simultaneously, the introduction of magnetic loss within the composite membrane enriches the loss mechanism and reduces secondary reflection of electromagnetic waves. However, due to the limitations of the composite membrane structure, the transmission path of electromagnetic waves within the composite material is difficult to extend effectively. Furthermore, due to the significant difference in conductivity between the reflective and absorbing layers, a large amount of electromagnetic waves reflected back to the absorbing layer by the highly conductive MXene layer are difficult to absorb effectively. Therefore, further research is needed to extend the transmission path of the composite membrane and enrich the loss mechanism. Summary of the Invention
[0006] To further enhance the electromagnetic wave absorption efficiency of the composite membrane, this invention introduces an aerogel structure into the asymmetric composite membrane structure. A highly conductive MXene membrane is composited with CNF / CNT / Fe3O4 aerogel, and the distribution of magnetic fillers in the aerogel is controlled by magnetic induction to prepare a magnetically gradient aerogel-membrane composite material. To reduce electromagnetic wave reflection, minimize secondary pollution, and obtain a high-performance, low-reflection electromagnetic shielding composite material, this invention utilizes a sol-gel conversion process to construct an aerogel-membrane composite material with a magnetic gradient through magnetic induction. This method is simple, environmentally friendly, and easy to operate.
[0007] The asymmetric structure of aerogel-film involved in this invention enables electromagnetic waves to form a "absorption-reflection-reabsorption" loss mechanism inside the composite material, thereby improving the electromagnetic shielding and absorption performance of the composite material.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: (1) FeCl3·6H2O is dissolved in ethylene glycol solution to obtain mixed solution A. Hexamethylenetetramine is added to mixed solution A and mixed evenly to obtain mixed solution B. Mixed solution B is reacted in an autoclave at 160-180 °C for 6-7 h. After the reaction, the mixture is washed with anhydrous ethanol and centrifuged at 6000-7000 rpm / min to collect the precipitate. The precipitate is dried (placed in a tube furnace) and calcined at 400-500 °C for 3-4 h under nitrogen atmosphere to obtain arrayed flower-like Fe3O4 particles. The mass ratio of FeCl3·6H2O to hexamethylenetetramine is 0.8:1-3 (preferably 0.8:3). (2) MXene is uniformly dispersed in deionized water to obtain an MXene dispersion. The MXene dispersion is then filtered through a PP filter membrane using a vacuum-assisted filtration method to prepare an MXene wet membrane. The MXene wet membrane is then molded and dried under a pressure of 40-50 kPa (preferably 50 kPa) (at room temperature for 24 h) to obtain an MXene membrane. The MXene is Ti3C2T prepared by in-situ hydrofluoric acid etching.X .
[0009] (3) The multi-walled carbon nanotubes and the arrayed flower-like Fe3O4 particles described in step (1) are ultrasonically dispersed in a benzyltrimethylammonium hydroxide solution with a concentration of 1.88-5M (preferably 1.88 M). Then, cellulose nanofibers are added and stirred to disperse evenly to obtain a mixed dispersion. The mixed dispersion is frozen at -10~-30℃ (preferably -18℃) for 12-18 h, thawed at room temperature, and stirred until it reaches a sol state. The sol-like mixed dispersion is poured into the mold for laying the MXene membrane described in step (2). The mold is placed under a magnet, and the magnetic field generated by the magnet induces the Fe3O4 particles to arrange 1-2 h (preferably a neodymium iron boron magnet to provide the magnetic field), and then freeze-set to obtain a shaped mixed dispersion; the mass ratio of the cellulose nanofibers, carbon nanotubes, and arrayed flower-like Fe3O4 particles is 85-95:5-15:10-50 (preferably 85:15:10), the cellulose nanofibers have a length of 5μm-10μm and a diameter of 5-100 nm; the mold is square.
[0010] (4) The shaped mixed dispersion described in step (3) is placed in deionized water at 0-15℃ (preferably 5℃) to coagulate and regenerate CNF / CNT / Fe3O4 regenerated gel-membrane. After being washed with deionized water, frozen and dried, the magnetic gradient aerogel-membrane composite material is obtained.
[0011] Furthermore, the Ti3C2T described in step (2) X The etching solution was prepared by mixing an aqueous HCl solution with LiF to obtain an etching solution. Ti3AlC2 was added to the etching solution to obtain a reaction solution. The reaction solution was then etched at 35-50℃ (preferably 35℃) for 24-36 hours (preferably 24 hours). After the reaction, the resulting reaction solution was centrifuged and washed to obtain a black sludge-like precipitate. The black sludge-like precipitate was mixed with water and ultrasonically exfoliated under an inert gas atmosphere (30 min, 40 kHz). The supernatant was collected by centrifugation and freeze-dried to obtain the Ti3C2T. X .
[0012] Furthermore, the volume of ethylene glycol in step (1) is 100-200 ml / g (preferably 200 ml / g) based on the mass of FeCl3·6H2O.
[0013] Furthermore, the PP filter membrane used in the vacuum-assisted filtration method in step (2) has a pore size of 0.22 μm and a filtration pressure of -0.08 to -0.1 MPa.
[0014] Furthermore, the amount of MXene added in step (2) is 5-20 mg / ml (preferably 5 mg / ml) based on deionized water.
[0015] Further, in step (2), the obtained MXene wet membrane is molded under a pressure of 50 kPa and dried at room temperature for 24 hours to obtain an MXene membrane.
[0016] Furthermore, the mold mentioned in step (3) is a square corundum crucible with mold dimensions of 1.5 cm × 4 cm × 2.5 mm. When pouring the sol-like mixed dispersion into the mold with the bottom lined with MXene film in step (3), the height of the dispersion in the mold is controlled to be 2.5 mm.
[0017] Furthermore, in step (3), the mixed dispersion is frozen at -18 °C for 18 h.
[0018] Furthermore, in step (3), the mass ratio of cellulose nanofibers, carbon nanotubes, and arrayed flower-like Fe3O4 particles is 85:15:10.
[0019] The present invention also provides an application of magnetic gradient aerogel-film composite material as an electromagnetic shielding material.
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) By adjusting the content of magnetic filler, the effective concentration of conductive filler is increased while constructing magnetic gradient, which significantly improves electromagnetic shielding performance, optimizes impedance matching, forms a loss mechanism of "gradient absorption-gradient reflection" and a shielding mechanism of absorption-reflection-reabsorption, and extends the electromagnetic wave transmission path.
[0021] (2) Composite materials with a magnetic gradient that gradually decreases from top to bottom have better electromagnetic shielding and absorption performance, achieving electromagnetic shielding with absorption as the active means.
[0022] (3) Aerogel-membrane composites have enhanced resistance to physical attacks and significantly improved compressive strength. Attached Figure Description
[0023] Figure 1 The total electromagnetic shielding effectiveness of Comparative Example 1 CNF / CNT aerogel and Comparative Example 2 CNF / CNT / Fe3O450 is shown. SE A , SE R , SE T Comparison of values and RTA test results.
[0024] Figure 2The total electromagnetic shielding effectiveness of Comparative Example 2 CNF / CNT / Fe3O450 and Example 5 CNF / CNT / Fe3O450-MX SE A , SE R , SE T Comparison of values and RTA test results.
[0025] Figure 3 The total electromagnetic shielding effectiveness of CNF / CNT / Fe3O450-MX in Example 5 and CNF / CNT / Fe3O450-MX(H) in Example 6 is... SE A , SE R , SE T Comparison of values and RTA test results. Detailed Implementation
[0026] The technical solution of the present invention will be further described in detail below through specific embodiments.
[0027] In this invention, unless otherwise specified, all equipment and raw materials are available from the market or commonly used in the industry. Unless otherwise specified, the methods in the following embodiments are conventional methods in the art.
[0028] Example 1
[0029] (1) Preparation process of array flower-shaped Fe3O4 particles: First, 0.8 g FeCl3·6H2O was added to 160 mL ethylene glycol solution and magnetically stirred until a homogeneous solution was formed. 3 g hexamethylenetetramine (HMT) was added and stirred evenly. The mixed solution was transferred to an autoclave and reacted at 160 °C for 7 h. After the reaction was completed, the autoclave was removed and cooled to room temperature. The reaction solution was washed three times with anhydrous ethanol and collected by centrifugation (7000 rpm / min). The precipitate was dried in an 80 °C forced-air oven for 24 h. Finally, the dried precipitate was placed in a tube furnace and calcined at 500 °C for 3 h under a nitrogen atmosphere. After naturally cooling to room temperature, black array flower-shaped Fe3O4 particles were obtained.
[0030] (2) Transfer 10 mL of HCl solution (9M) to a polytetrafluoroethylene beaker, weigh 0.75 g of LiF and add it to the HCl solution. Stir for 10 min (500 rpm) until completely dissolved to obtain the etching solution. Add 0.5 g of Ti3AlC2 to the etching solution and stir evenly (500 rpm). Then, transfer the reaction solution to a 35 ℃ water bath and etch for 24 h (500 rpm). After the reaction is complete, centrifuge the reaction solution with deionized water (3500 rpm, 5 min) until the upper liquid is neutral, and obtain a black sludge-like precipitate. Add 5 mL of deionized water to the above black sludge-like precipitate to prepare a dispersion. Sonicate the dispersion for 30 min (40 kHz) under N2 protection. After the dispersion is completed, centrifuge the dispersion for 15 min (7000 rpm). Collect the upper dispersion and freeze-dry it in a freeze dryer for 36 h to obtain Ti3C2T. X (MXene).
[0031] 100 mg of MXene (Ti3C2T prepared by in-situ hydrofluoric acid etching) was added. X The MXene dispersion was uniformly dispersed in 20 mL of deionized water, and the MXene wet membrane was prepared by vacuum-assisted filtration (filtration pressure of -0.1 MPa) through a PP filter membrane with a pore size of 0.22 μm. The obtained MXene membrane was then molded and dried at a pressure of 50 kPa for 24 h. After being cut to the size of the mold, the MXene membrane was placed at the bottom of the mold, which was a square corundum crucible with dimensions of 1.5 cm × 4 cm × 2.5 mm.
[0032] (3) 30 mg of CNT (multi-walled carbon nanotubes purchased from Nanocyl SA, Belgium, model NC7000) and 20 mg of Fe3O4 were ultrasonically dispersed in a 1.88 M benzyltrimethylammonium hydroxide solution. Then, 170 mg of CNF (purchased from Zhongshan Nanofiber New Materials Co., Ltd., model 1904H, with a length >5 μm and a diameter of 5-100 nm, CNF exhibits a flexible filamentous structure with a network structure, confirmed by scanning electron microscopy to have a length >5 μm and a diameter between 5-100 nm) was added and stirred for 30 min. The CNF / CNT ratio was 85:15, and the concentration of the CNF / CNT dispersion was 6 wt%. The mass of Fe3O4 accounted for 10 wt% of the total mass of CNF / CNT. The mixed dispersion was frozen at -18 ℃ for 18 h. The mixed dispersion was thawed at room temperature and stirred for 30 min, at which point the dispersion became a sol. Then, the CNF / CNT / Fe3O4 dispersion was poured into a mold with an MXene film at the bottom. The height of the dispersion in the mold was controlled to be 2.5 mm. An external magnetic field was introduced by placing the mold under a national standard N52 neodymium iron boron magnet. The magnetic field induced the Fe3O4 particles to align for 2 h.
[0033] (4) The mixed dispersion poured into the mold and subjected to magnetic induction was placed in a -18 ℃ freezer for 12 h to fix the shape. Then the fixed mixed dispersion was placed in deionized water at 5 ℃ to solidify and regenerate, thus obtaining CNF / CNT / Fe3O4 regenerated gel-membrane.
[0034] (5) The obtained regenerated gel-membrane was washed with deionized water, frozen at -18°C, and then dried in a freeze dryer to obtain a magnetic gradient aerogel-membrane composite material (referred to as CNF / CNT / Fe3O410-MX in this embodiment).
[0035] Example 2
[0036] (1) Preparation process of array flower-shaped Fe3O4 particles: First, 0.8 g FeCl3·6H2O was added to 160 mL ethylene glycol solution and magnetically stirred until a homogeneous solution was formed. 3 g hexamethylenetetramine (HMT) was added and stirred evenly. The mixed solution was transferred to an autoclave and reacted at 160 °C for 7 h. After the reaction was completed, the autoclave was removed and cooled to room temperature. The reaction solution was washed three times with anhydrous ethanol and collected by centrifugation (7000 rpm / min). The precipitate was dried in an 80 °C forced-air oven for 24 h. Finally, the dried precipitate was placed in a tube furnace and calcined at 500 °C for 3 h under a nitrogen atmosphere. After naturally cooling to room temperature, black array flower-shaped Fe3O4 particles were obtained.
[0037] (2) Transfer 10 mL of HCl solution (9M) to a polytetrafluoroethylene beaker, weigh 0.75 g of LiF and add it to the HCl solution, stirring for 10 min (500 rpm) until completely dissolved. Add 0.5 g of Ti3AlC2 to the etching solution and stir evenly (500 rpm). Then, transfer the reaction solution to a 35 ℃ water bath and etch for 24 h (500 rpm). After the reaction, the reaction solution is washed repeatedly by centrifugation with deionized water (3500 rpm, 5 min) until the upper liquid is neutral, resulting in a black sludge-like precipitate. Add 5 mL of deionized water to the above black sludge-like precipitate to prepare a dispersion, and ultrasonically peel it off for 30 min (40 kHz) under N2 protection. After the removal, centrifuge the dispersion for 15 min (7000 rpm), collect the upper dispersion and freeze-dry it in a freeze dryer for 36 h to obtain Ti3C2T. X (MXene).
[0038] 100 mg of MXene (prepared by in-situ hydrofluoric acid etching) was used to prepare Ti3C2T. X The MXene dispersion was uniformly dispersed in 20 mL of deionized water, and the MXene wet membrane was prepared by vacuum-assisted filtration (filtration pressure of -0.1 MPa) through a PP filter membrane with a pore size of 0.22 μm. The obtained MXene membrane was then molded and dried at a pressure of 50 kPa for 24 h. After being cut to the size of the mold, the MXene membrane was placed at the bottom of the mold, which was a square corundum crucible with dimensions of 1.5 cm × 4 cm × 2.5 mm.
[0039] (3) 30 mg of CNT (carbon nanotubes purchased from Nanocyl SA, Belgium, model NC7000) and 40 mg of Fe3O4 were ultrasonically dispersed in a 1.88 M benzyltrimethylammonium hydroxide solution. Then, 170 mg of CNF (purchased from Zhongshan Nanofiber New Materials Co., Ltd., model 1904H, with a length >5 μm and a diameter of 5-100 nm) was added and stirred for 30 min. The CNF / CNT ratio was 85:15, and the concentration of the CNF / CNT dispersion was 6 wt%. The mass of Fe3O4 accounted for 20 wt% of the total mass of CNF / CNT. The mixed dispersion was frozen at -18 ℃ for 18 h. The mixed dispersion was thawed at room temperature and stirred for 30 min, at which point the dispersion became a sol. Then, the CNF / CNT / Fe3O4 dispersion was poured into a mold with an MXene film at the bottom. The height of the dispersion in the mold was controlled to be 2.5 mm. An external magnetic field was introduced by placing the mold under a national standard N52 neodymium iron boron magnet. The magnetic field induced the Fe3O4 particles to align for 2 h.
[0040] (4) The mixed dispersion poured into the mold and subjected to magnetic induction was placed in a -18 ℃ freezer for 12 h to fix the shape. Then the fixed mixed dispersion was placed in deionized water at 5 ℃ to solidify and regenerate, thus obtaining CNF / CNT / Fe3O4 regenerated gel-membrane.
[0041] (5) The obtained regenerated gel-membrane was washed with deionized water, frozen at -18°C, and then dried in a freeze dryer to obtain a magnetic gradient aerogel-membrane composite material (referred to as CNF / CNT / Fe3O420-MX in this embodiment).
[0042] Example 3
[0043] (1) Preparation process of array flower-shaped Fe3O4 particles: First, 0.8 g FeCl3·6H2O was added to 160 mL ethylene glycol solution and magnetically stirred until a homogeneous solution was formed. 3 g hexamethylenetetramine (HMT) was added and stirred evenly. The mixed solution was transferred to an autoclave and reacted at 160 °C for 7 h. After the reaction was completed, the autoclave was removed and cooled to room temperature. The reaction solution was washed three times with anhydrous ethanol and collected by centrifugation (7000 rpm / min). The precipitate was dried in an 80 °C forced-air oven for 24 h. Finally, the dried precipitate was placed in a tube furnace and calcined at 500 °C for 3 h under a nitrogen atmosphere. After naturally cooling to room temperature, black array flower-shaped Fe3O4 particles were obtained.
[0044] (2) Transfer 10 mL of HCl solution (9M) to a polytetrafluoroethylene beaker, weigh 0.75 g of LiF and add it to the HCl solution, stirring for 10 min (500 rpm) until completely dissolved. Add 0.5 g of Ti3AlC2 to the etching solution and stir evenly (500 rpm). Then, transfer the reaction solution to a 35 ℃ water bath and etch for 24 h (500 rpm). After the reaction, the reaction solution is washed repeatedly by centrifugation with deionized water (3500 rpm, 5 min) until the upper liquid is neutral, resulting in a black sludge-like precipitate. Add 5 mL of water to the above black sludge-like precipitate to prepare a dispersion, and ultrasonically peel it off for 30 min (40 kHz) under N2 protection. After the removal, centrifuge the dispersion for 15 min (7000 rpm), collect the upper dispersion and freeze-dry it in a freeze dryer for 36 h to obtain Ti3C2T. X (MXene).
[0045] 100 mg of MXene (prepared by in-situ hydrofluoric acid etching) was used to prepare Ti3C2T. XThe MXene dispersion was uniformly dispersed in 20 mL of deionized water, and the MXene wet membrane was prepared by vacuum-assisted filtration (filtration pressure of -0.1 MPa) through a PP filter membrane with a pore size of 0.22 μm. The obtained MXene membrane was then molded and dried at a pressure of 50 kPa for 24 h. After being cut to the size of the mold, the MXene membrane was placed at the bottom of the mold, which was a square corundum crucible with dimensions of 1.5 cm × 4 cm × 2.5 mm.
[0046] (3) 30 mg of CNT (carbon nanotubes purchased from Nanocyl SA, Belgium, model NC7000) and 60 mg of Fe3O4 were ultrasonically dispersed in a 1.88 M benzyltrimethylammonium hydroxide solution. Then, 170 mg of CNF (purchased from Zhongshan Nanofiber New Materials Co., Ltd., model 1904H, with a length >5 μm and a diameter of 5-100 nm) was added and stirred for 30 min. The CNF / CNT ratio was 85:15, and the concentration of the CNF / CNT dispersion was 6 wt%. The mass of Fe3O4 accounted for 30 wt% of the total mass of CNF / CNT. The mixed dispersion was frozen at -18 ℃ for 18 h. The mixed dispersion was thawed at room temperature and stirred for 30 min, at which point the dispersion became a sol. Then, the CNF / CNT / Fe3O4 dispersion was poured into a mold with an MXene film at the bottom. The height of the dispersion in the mold was controlled to be 2.5 mm. An external magnetic field was introduced by placing the mold under a national standard N52 neodymium iron boron magnet. The magnetic field induced the Fe3O4 particles to align for 2 h.
[0047] (4) The mixed dispersion poured into the mold and subjected to magnetic induction was placed in a -18 ℃ freezer for 12 h to fix the shape. Then the fixed mixed dispersion was placed in deionized water at 5 ℃ to solidify and regenerate, thus obtaining CNF / CNT / Fe3O4 regenerated gel-membrane.
[0048] (5) The obtained regenerated gel-membrane was washed with deionized water, frozen at -18°C, and then dried in a freeze dryer to obtain a magnetic gradient aerogel-membrane composite material (referred to as CNF / CNT / Fe3O430-MX in this embodiment).
[0049] Example 4
[0050] (1) Preparation process of array flower-shaped Fe3O4 particles: First, 0.8 g FeCl3·6H2O was added to 160 mL ethylene glycol solution and magnetically stirred until a homogeneous solution was formed. 3 g hexamethylenetetramine (HMT) was added and stirred evenly. The mixed solution was transferred to an autoclave and reacted at 160 °C for 7 h. After the reaction was completed, the autoclave was removed and cooled to room temperature. The reaction solution was washed three times with anhydrous ethanol and collected by centrifugation (7000 rpm / min). The precipitate was dried in an 80 °C forced-air oven for 24 h. Finally, the dried precipitate was placed in a tube furnace and calcined at 500 °C for 3 h under a nitrogen atmosphere. After naturally cooling to room temperature, black array flower-shaped Fe3O4 particles were obtained.
[0051] (2) Transfer 10 mL of HCl solution (9M) to a polytetrafluoroethylene beaker, weigh 0.75 g of LiF and add it to the HCl solution, stirring for 10 min (500 rpm) until completely dissolved. Add 0.5 g of Ti3AlC2 to the etching solution and stir evenly (500 rpm). Then, transfer the reaction solution to a 35 ℃ water bath and etch for 24 h (500 rpm). After the reaction, the reaction solution is washed repeatedly by centrifugation with deionized water (3500 rpm, 5 min) until the upper liquid is neutral, resulting in a black sludge-like precipitate. Add 5 mL of water to the above black sludge-like precipitate to prepare a dispersion, and ultrasonically peel it off for 30 min (40 kHz) under N2 protection. After the removal, centrifuge the dispersion for 15 min (7000 rpm), collect the upper dispersion and freeze-dry it in a freeze dryer for 36 h to obtain Ti3C2T. X (MXene).
[0052] 100 mg of MXene (prepared by in-situ hydrofluoric acid etching) was used to prepare Ti3C2T. X The MXene dispersion was uniformly dispersed in 20 mL of deionized water, and the MXene wet membrane was prepared by vacuum-assisted filtration (filtration pressure of -0.1 MPa) through a PP filter membrane with a pore size of 0.22 μm. The obtained MXene membrane was then molded and dried at a pressure of 50 kPa for 24 h. After being cut to the size of the mold, the MXene membrane was placed at the bottom of the mold, which was a square corundum crucible with dimensions of 1.5 cm × 4 cm × 2.5 mm.
[0053] (3) 30 mg of CNT (carbon nanotubes purchased from Nanocyl SA, Belgium, model NC7000) and 80 mg of Fe3O4 were ultrasonically dispersed in a 1.88 M benzyltrimethylammonium hydroxide solution. Then, 170 mg of CNF (purchased from Zhongshan Nanofiber New Materials Co., Ltd., model 1904H, with a length >5 μm and a diameter of 5-100 nm) was added and stirred for 30 min. The CNF / CNT ratio was 85:15, and the concentration of the CNF / CNT dispersion was 6 wt%. The mass of Fe3O4 accounted for 40 wt% of the total mass of CNF / CNT. The mixed dispersion was frozen at -18 ℃ for 18 h. The mixed dispersion was thawed at room temperature and stirred for 30 min, at which point the dispersion became a sol. Then, the CNF / CNT / Fe3O4 dispersion was poured into a mold with an MXene film at the bottom. The height of the dispersion in the mold was controlled to be 2.5 mm. An external magnetic field was introduced by placing the mold under a national standard N52 neodymium iron boron magnet. The magnetic field induced the Fe3O4 particles to align for 2 h.
[0054] (4) The mixed dispersion poured into the mold and subjected to magnetic induction was placed in a -18 ℃ freezer for 12 h to fix the shape. Then the fixed mixed dispersion was placed in deionized water at 5 ℃ to solidify and regenerate, thus obtaining CNF / CNT / Fe3O4 regenerated gel-membrane.
[0055] (5) The obtained regenerated gel-membrane was washed with deionized water, frozen at -18°C, and then dried in a freeze dryer to obtain a magnetic gradient aerogel-membrane composite material (referred to as CNF / CNT / Fe3O440-MX in this embodiment).
[0056] Example 5
[0057] (1) Preparation process of array flower-shaped Fe3O4 particles: First, 0.8 g FeCl3·6H2O was added to 160 mL ethylene glycol solution and magnetically stirred until a homogeneous solution was formed. 3 g hexamethylenetetramine (HMT) was added and stirred evenly. The mixed solution was transferred to an autoclave and reacted at 160 °C for 7 h. After the reaction was completed, the autoclave was removed and cooled to room temperature. The reaction solution was washed three times with anhydrous ethanol and collected by centrifugation (7000 rpm / min). The precipitate was dried in an 80 °C forced-air oven for 24 h. Finally, the dried precipitate was placed in a tube furnace and calcined at 500 °C for 3 h under a nitrogen atmosphere. After naturally cooling to room temperature, black array flower-shaped Fe3O4 particles were obtained.
[0058] (2) Transfer 10 mL of HCl solution (9M) to a polytetrafluoroethylene beaker, weigh 0.75 g of LiF and add it to the HCl solution, stirring for 10 min (500 rpm) until completely dissolved. Add 0.5 g of Ti3AlC2 to the etching solution and stir evenly (500 rpm). Then, transfer the reaction solution to a 35 ℃ water bath and etch for 24 h (500 rpm). After the reaction, the reaction solution is washed repeatedly by centrifugation with deionized water (3500 rpm, 5 min) until the upper liquid is neutral, resulting in a black sludge-like precipitate. Add 5 mL of water to the above black sludge-like precipitate to prepare a dispersion, and ultrasonically peel it off for 30 min (40 kHz) under N2 protection. After the removal, centrifuge the dispersion for 15 min (7000 rpm), collect the upper dispersion and freeze-dry it in a freeze dryer for 36 h to obtain Ti3C2T. X (MXene).
[0059] 100 mg of MXene (prepared by in-situ hydrofluoric acid etching) was used to prepare Ti3C2T. X The MXene dispersion was uniformly dispersed in 20 mL of deionized water, and the MXene wet membrane was prepared by vacuum-assisted filtration (filtration pressure of -0.1 MPa) through a PP filter membrane with a pore size of 0.22 μm. The obtained MXene membrane was then molded and dried at a pressure of 50 kPa for 24 h. After being cut to the size of the mold, the MXene membrane was placed at the bottom of the mold, which was a square corundum crucible with dimensions of 1.5 cm × 4 cm × 2.5 mm.
[0060] (3) 30 mg of CNT (carbon nanotubes purchased from Nanocyl SA, Belgium, model NC7000) and 100 mg of Fe3O4 were ultrasonically dispersed in a 1.88 M benzyltrimethylammonium hydroxide solution. Then, 170 mg of CNF (purchased from Zhongshan Nanofiber New Materials Co., Ltd., model 1904H, with a length >5 μm and a diameter of 5-100 nm) was added and stirred for 30 min. The CNF / CNT ratio was 85:15, and the concentration of the CNF / CNT dispersion was 6 wt%. The mass of Fe3O4 accounted for 50 wt% of the total mass of CNF / CNT. The mixed dispersion was frozen at -18 ℃ for 18 h. The mixed dispersion was thawed at room temperature and stirred for 30 min, at which point the dispersion became a sol. Then, the CNF / CNT / Fe3O4 dispersion was poured into a mold with an MXene film at the bottom. The height of the dispersion in the mold was controlled to be 2.5 mm. An external magnetic field was introduced by placing the mold under a national standard N52 neodymium iron boron magnet. The magnetic field induced the Fe3O4 particles to align for 2 h.
[0061] (4) The mixed dispersion poured into the mold and subjected to magnetic induction was placed in a -18 ℃ freezer for 12 h to fix the shape. Then the fixed mixed dispersion was placed in deionized water at 5 ℃ to solidify and regenerate, thus obtaining CNF / CNT / Fe3O4 regenerated gel-membrane.
[0062] (5) The obtained regenerated gel-membrane was washed with deionized water, frozen at -18°C, and then dried in a freeze dryer to obtain a magnetic gradient aerogel-membrane composite material (denoted as CNF / CNT / Fe3O450-MX).
[0063] Example 6
[0064] (1) Preparation process of array flower-shaped Fe3O4 particles: First, 0.8 g FeCl3·6H2O was added to 160 mL ethylene glycol solution and magnetically stirred until a homogeneous solution was formed. 3 g hexamethylenetetramine (HMT) was added and stirred evenly. The mixed solution was transferred to an autoclave and reacted at 160 °C for 7 h. After the reaction was completed, the autoclave was removed and cooled to room temperature. The reaction solution was washed three times with anhydrous ethanol and collected by centrifugation (7000 rpm / min). The precipitate was dried in an 80 °C forced-air oven for 24 h. Finally, the dried precipitate was placed in a tube furnace and calcined at 500 °C for 3 h under a nitrogen atmosphere. After naturally cooling to room temperature, black array flower-shaped Fe3O4 particles were obtained.
[0065] (2) Transfer 10 mL of HCl solution (9M) to a polytetrafluoroethylene beaker, weigh 0.75 g of LiF and add it to the HCl solution, stirring for 10 min (500 rpm) until completely dissolved. Add 0.5 g of Ti3AlC2 to the etching solution and stir evenly (500 rpm). Then, transfer the reaction solution to a 35 ℃ water bath and etch for 24 h (500 rpm). After the reaction, the reaction solution is washed repeatedly by centrifugation with deionized water (3500 rpm, 5 min) until the upper liquid is neutral, resulting in a black sludge-like precipitate. Add 5 mL of water to the above black sludge-like precipitate to prepare a dispersion, and ultrasonically peel it off for 30 min (40 kHz) under N2 protection. After the removal, centrifuge the dispersion for 15 min (7000 rpm), collect the upper dispersion and freeze-dry it in a freeze dryer for 36 h to obtain Ti3C2T. X (MXene).
[0066] 100 mg of MXene (prepared by in-situ hydrofluoric acid etching) was used to prepare Ti3C2T. XThe MXene dispersion was uniformly dispersed in 20 mL of deionized water, and the MXene wet membrane was prepared by vacuum-assisted filtration (filtration pressure of -0.1 MPa) through a PP filter membrane with a pore size of 0.22 μm. The obtained MXene membrane was then molded and dried at a pressure of 50 kPa for 24 h. After being cut to the size of the mold, the MXene membrane was placed at the bottom of the mold, which was a square corundum crucible with dimensions of 1.5 cm × 4 cm × 2.5 mm.
[0067] (3) 30 mg of CNTs (carbon nanotubes purchased from Nanocyl SA, Belgium, model NC7000) and 100 mg of Fe3O4 were ultrasonically dispersed in a 1.88 M benzyltrimethylammonium hydroxide solution. Then, 170 mg of CNF (purchased from Zhongshan Nanofiber New Materials Co., Ltd., model 1904H, with a length >5 μm and a diameter of 5-100 nm) was added and stirred for 30 min. The CNF / CNT ratio was 85:15, and the concentration of the CNF / CNT dispersion was 6 wt%. The mass percentage of Fe3O4 in the total mass of CNF / CNT was 50 wt%. The mixed dispersion was frozen at -18 ℃ for 18 h. The mixed dispersion was thawed at room temperature and stirred for 30 min, at which point the dispersion became a sol.
[0068] (4) Subsequently, the CNF / CNT / Fe3O4 dispersion was poured into a mold with an MXene membrane already laid at the bottom. The height of the dispersion in the mold was controlled to be 2.5 mm. The mixed dispersion poured into the mold was placed in a -18 ℃ freezer for 12 h to solidify. Then, the solidified mixed dispersion was placed in deionized water at 5 ℃ for coagulation and regeneration to obtain CNF / CNT / Fe3O4 regenerated gel-membrane. The obtained regenerated gel-membrane was washed, frozen, and freeze-dried to obtain CNF / CNT / Fe3O450-MX(H) aerogel-membrane composite material. Fe3O4 was not induced by a magnetic field to be uniformly distributed in the aerogel. It was named CNF / CNT / Fe3O450-MX(H).
[0069] Comparative Example 1
[0070] (1) Take 30 mg of CNT (carbon nanotubes purchased from Nanocyl SA, Belgium, model NC7000) and ultrasonically disperse it in 1.88 M benzyltrimethylammonium hydroxide. Then add 170 mg of CNF (purchased from Zhongshan Nanofiber New Material Co., Ltd., model 1904H, with a length >5 μm and a diameter of 5-100 nm) and stir for 30 min. Freeze the mixture at -18 ℃ for 18 h. The CNF / CNT ratio is 85:15 and the concentration of CNF / CNT dispersion is 6 wt%. Thaw the mixture at room temperature and stir for 30 min. At this time, the dispersion becomes viscous. Then pour the CNF / CNT dispersion into a mold with a size of 1.5 cm × 4 cm and control the height of the dispersion in the mold to be 2.5 mm.
[0071] (2) The mixed dispersion poured into the mold was frozen in a -18 ℃ refrigerator for 12 h to set the shape. Then the set mixed dispersion was placed in deionized water at 4 ℃ to solidify and regenerate, and CNF / CNT regenerated gel was obtained.
[0072] (3) Wash the CNF / CNT gel repeatedly with deionized water until the washing solution is neutral. Finally, freeze the CNF / CNT gel and then freeze-dry it to obtain CNF / CNT aerogel.
[0073] Comparative Example 2
[0074] (1) Preparation process of array flower-shaped Fe3O4 particles: First, 0.8 g FeCl3·6H2O was added to 160 mL ethylene glycol solution and magnetically stirred until a homogeneous solution was formed. 3 g hexamethylenetetramine (HMT) was added and stirred evenly. The mixed solution was transferred to an autoclave and reacted at 160 °C for 7 h. After the reaction was completed, the autoclave was removed and cooled to room temperature. The reaction solution was washed three times with ethanol and collected by centrifugation (7000 rpm / min). The precipitate was dried in an 80 °C forced-air oven for 24 h. Finally, the dried precipitate was placed in a tube furnace and calcined at 500 °C for 3 h under a nitrogen atmosphere. After naturally cooling to room temperature, black array flower-shaped Fe3O4 particles were obtained.
[0075] (2) 30 mg of CNTs (carbon nanotubes purchased from Nanocyl SA, Belgium, model NC7000) and 100 mg of Fe3O4 were ultrasonically dispersed in a 1.88 M benzyltrimethylammonium hydroxide solution. Then, 170 mg of CNF (purchased from Zhongshan Nanofiber New Materials Co., Ltd., model 1904H, with a length >5 μm and a diameter of 5-100 nm) was added and stirred for 30 min. The CNF / CNT ratio was 85:15, and the mass percentage of Fe3O4 in the total mass of CNF / CNT was 50 wt%. The mixed dispersion was frozen at -18 ℃ for 18 h. The mixed dispersion was thawed at room temperature and stirred for 30 min, at which point the dispersion became a sol.
[0076] (3) Subsequently, the CNF / CNT / Fe3O4 dispersion was poured into a mold, and the height of the dispersion in the mold was controlled to be 2.5 mm. At the same time, an external magnetic field was introduced by placing the mold under the magnet using a neodymium iron boron magnet. The magnetic field induced the Fe3O4 particles to align for 2 h. The mixed dispersion poured into the mold and subjected to magnetic induction was placed in a -18 ℃ freezer for 12 h to fix the shape. Then, the fixed mixed dispersion was placed in deionized water at 5 ℃ for coagulation and regeneration to obtain CNF / CNT / Fe3O4 regenerated gel. The obtained regenerated gel was washed, frozen, and freeze-dried to obtain CNF / CNT / Fe3O4 50 magnetic gradient aerogel composite material.
[0077] The performance of the composite membrane samples from Examples 1-6 and Comparative Examples 1-2 was tested, and the test results are shown in Table 1: Table 1. Measurement results of composite membranes in Examples 1-6 and Comparative Examples 1-2
[0078] This invention utilizes a sol-gel conversion process to construct an aerogel-film composite material with a magnetic gradient through magnetic induction. The direction and intensity of the magnetic gradient are constructed by adjusting the content and distribution of Fe3O4. By controlling the content of magnetic fillers, the effective concentration of conductive fillers is increased while constructing the magnetic gradient, significantly improving electromagnetic shielding performance, optimizing impedance matching, and forming a "gradient absorption-gradient reflection" loss mechanism and an absorption-reflection-reabsorption shielding mechanism, thus extending the electromagnetic wave transmission path. A comparison of Comparative Example 1 and Comparative Example 2 shows that the conductivity and electromagnetic shielding performance of the composite material increase with the addition of magnetic particles. Magnetic particles drive cellulose upwards, increasing the relative content of CNTs in the lower part of the aerogel and increasing their overlap rate. The carbon-based conductive network formed by CNTs in the lower part of the aerogel gradually becomes complete, thereby enhancing the overall electromagnetic shielding effectiveness of the composite material. A comparison of Comparative Example 2 and Example 5 shows that the aerogel and the highly conductive MXene film together form a conductivity gradient with gradually decreasing conductivity from bottom to top, forming a "gradient absorption-gradient reflection" loss mechanism, resulting in higher electromagnetic shielding effectiveness for the composite material. The construction of a magnetic gradient significantly improves the conductivity and electromagnetic shielding effectiveness of the composite material. A comparison of Examples 5 and 6 shows that by magnetically inducing a top-down magnetic gradient structure in the aerogel-film composite material, the impedance matching between the composite material and the surrounding medium is adjusted, providing more possibilities for incident electromagnetic waves to enter the material's interior. Magnetic and conductive fillers provide multiple loss mechanisms and loss interfaces for the incident electromagnetic waves, forming a "gradient absorption-gradient reflection" loss mechanism, thus resulting in more outstanding overall electromagnetic shielding and absorption effectiveness.
[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Other variations and modifications are possible without departing from the technical solutions described in the claims.
Claims
1. A magnetic gradient aerogel-membrane composite material, characterized in that, The preparation method of the magnetic gradient aerogel-film composite material includes the following steps: (1) FeCl3·6H2O is dissolved in ethylene glycol solution to obtain mixed solution A. Hexamethylenetetramine is added to mixed solution A and mixed evenly to obtain mixed solution B. Mixed solution B is reacted in an autoclave at 160-180 °C for 6-7 h. After the reaction, it is washed with anhydrous ethanol and centrifuged at 6000-7000 rpm / min to collect the precipitate. The precipitate is dried and calcined at 400-500 °C for 3-4 h under nitrogen atmosphere to obtain arrayed flower-like Fe3O4 particles. The mass ratio of FeCl3·6H2O to hexamethylenetetramine is 0.8:1-3. (2) MXene is uniformly dispersed in deionized water to obtain an MXene dispersion. The MXene dispersion is then filtered through a PP filter membrane using a vacuum-assisted filtration method to prepare an MXene wet membrane. The MXene wet membrane is then molded and dried under a pressure of 40-50 kPa to obtain an MXene membrane. The MXene is Ti3C2T prepared by in-situ hydrofluoric acid etching. X . (3) The multi-walled carbon nanotubes and the arrayed flower-like Fe3O4 particles described in step (1) are ultrasonically dispersed in a benzyltrimethylammonium hydroxide solution with a concentration of 1.88-5M. Then, cellulose nanofibers are added and stirred to disperse evenly to obtain a mixed dispersion. The mixed dispersion is frozen at -10~-30℃ for 12-18 h, thawed at room temperature, and stirred until it becomes a sol. The sol-like mixed dispersion is poured into the mold for the MXene membrane in step (2). The mold is placed under a magnet, and the magnetic field generated by the magnet induces the Fe3O4 particles to align for 1-2 h. Then, it is frozen to obtain a shaped mixed dispersion. The mass ratio of the cellulose nanofibers, carbon nanotubes, and arrayed flower-like Fe3O4 particles is 85-95:5-15:10-50. The length of the cellulose nanofibers is 5 μm-10 μm and the diameter is 5-100 nm. The mold is square. (4) The shaped mixed dispersion described in step (3) is placed in deionized water at 0-15℃ to coagulate and regenerate CNF / CNT / Fe3O4 regenerated gel-membrane, and then washed with deionized water, frozen and dried to obtain the magnetic gradient aerogel-membrane composite material.
2. The magnetic gradient aerogel-film composite material as described in claim 1, characterized in that, The Ti3C2T mentioned in step (2) X The etching solution was prepared by mixing an aqueous HCl solution with LiF to obtain an etching solution. Ti3AlC2 was added to the etching solution to obtain a reaction solution. The reaction solution was etched at 35-50℃ for 24-36 hours. After the reaction, the resulting reaction solution was centrifuged and washed to obtain a black sludge-like precipitate. The black sludge-like precipitate was mixed with water and ultrasonically peeled off under an inert gas atmosphere. The supernatant was collected by centrifugation and freeze-dried to obtain the Ti3C2T. X .
3. The magnetic gradient aerogel-film composite material as described in claim 1, characterized in that, The volume of ethylene glycol in step (1) is 100-200 ml / g based on the mass of FeCl3·6H2O.
4. The magnetic gradient aerogel-film composite material as described in claim 1, characterized in that, The PP filter membrane used in the vacuum-assisted filtration method in step (2) has a pore size of 0.22 μm and a filtration pressure of -0.08 to -0.1 MPa.
5. The magnetic gradient aerogel-film composite material as described in claim 1, characterized in that, The amount of MXene added in step (2) is 5-20 mg / ml based on deionized water.
6. The magnetic gradient aerogel-film composite material as described in claim 1, characterized in that, In step (2), the obtained MXene wet membrane is molded under a pressure of 50 kPa and dried at room temperature for 24 hours to obtain the MXene membrane.
7. The magnetic gradient aerogel-film composite material as described in claim 1, characterized in that, The mold mentioned in step (3) is a square corundum crucible with a size of 1.5 cm × 4 cm × 2.5 mm. When pouring the sol-like mixed dispersion into the mold with the bottom lined with MXene film in step (3), the height of the dispersion in the mold is controlled to be 2.5 mm.
8. The magnetic gradient aerogel-film composite material as described in claim 1, characterized in that, In step (3), the mixed dispersion is frozen at -18 ℃ for 18 h.
9. The magnetic gradient aerogel-film composite material as described in claim 1, characterized in that, The mass ratio of cellulose nanofibers, carbon nanotubes, and arrayed flower-like Fe3O4 particles in step (3) is 85:15:
10.
10. The application of the magnetic gradient aerogel-film composite material as described in claim 1 as an electromagnetic shielding material.